2013
DOI: 10.12693/aphyspola.123.761
|View full text |Cite
|
Sign up to set email alerts
|

EPR and Optical Spectroscopy of Iron Doped Mixed Alkali Cadmium Phosphate Glasses

Abstract: Iron doped mixed alkali cadmium phosphate (LiNaCdP) glasses of the following chemical composition xLi2O + (20-x)Na2O + 20CdO + 59.5P2O5 + 0.5Fe2O3 (5 < x < 15) were prepared by melt quenching technique to study the mixed alkali eect. To manifest the mixed alkali eect, electron paramagnetic resonance and optical absorption studies were carried out at room temperature for these phosphate glasses. The physical and optical properties of these glasses have been evaluated. The results accomplished for the present gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, if we consider melting glass as a solvent, phosphate glasses are more acceptor than silicate or borate glasses for O 2− ions [6] and have a lower tendency to crystalline formation [7]. Although they have a potential use in the fabrication of solidstate lasers and as potential cathode materials in Li-ion batteries [8,9], the partly low chemical stability of these glasses restricts their performance [10]. It has been observed that the addition of some TMOs or alkali and alkaline earth oxides into the glass structure can improve the chemical stability of the composition [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if we consider melting glass as a solvent, phosphate glasses are more acceptor than silicate or borate glasses for O 2− ions [6] and have a lower tendency to crystalline formation [7]. Although they have a potential use in the fabrication of solidstate lasers and as potential cathode materials in Li-ion batteries [8,9], the partly low chemical stability of these glasses restricts their performance [10]. It has been observed that the addition of some TMOs or alkali and alkaline earth oxides into the glass structure can improve the chemical stability of the composition [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hence these glasses can be used as optical bandpass filters in the visible region with two different wavelengths. 27,28…”
Section: Optical Transmission Spectramentioning
confidence: 99%